Sustainability performance of organization: Mediating role of knowledge management - I Ketut Setia Sapta; I Nengah Sudja; I Nengah Landra; Ni Wayan Rustiarini (Economies, 2021)
Research about sustainable performance and its impact on the organization's economic, social, and environmental development has attracted the attention of many scholars. However, the research investigating the relationship between sustainable performance from traditional organizations based on local culture is still underdeveloped. This study aimed to examine the relationship among organizational culture and leadership styles with knowledge management and sustainable performance. Moreover, this study investigates knowledge management's role as a mediating variable in the relationship between organizational culture, leadership style, and sustainable performance. This study adopted a quantitative approach using the purposive sampling method with a questionnaire distributed to 99 respondents in Bali Province, Indonesia. The analysis technique was SEM-PLS. The results revealed that organizational culture and transformational leadership have significant effects on knowledge management. This study also proves that knowledge management mediates the relationship between organizational culture and sustainable performance, as well as the relationship between leadership style and sustainable performance. Theoretically, this study confirms the knowledge-based theory about knowledge management practices and sustainability performance. The present study also highlights the characteristics of organizational culture in traditional organizations and the effectiveness of transformational leadership to achieve sustainable organizational performance. Practically, the results provide insights to aid governments and regulators in continuously implementing knowledge management to achieve sustainable performance.
Keywords: 330; Indonesia; organizational culture; Subak; transformational leadership; Tri Hita Karana